Textile recycling: A systems perspective - Hawley, Jana M. (Woodhead Publishing Limited, UK, 2008)
The juxtaposition of a throw-away society with the realization that natural resources are threatened is a vivid illustration of the perplexing problem of contemporary lifestyle. As we consider the case of textile and apparel recycling it becomes apparent that the process impacts many entities and contributes significantly, in a broader sense, to the social responsibility of contemporary culture. By recycling, companies can realize larger profits because they avoid charges associated with dumping in landfills while at the same time recycling of textiles also contributes to goodwill associated with environmentalism, employment for marginally employable laborers, contributions to charities and disaster relief, and the movement of used clothing to areas of the world where clothing is needed. Because textiles are nearly 100% recyclable, nothing in the textile and apparel industry should be wasted. Harley Davidson jackets go to Japan, neckties go to Vietnam, raincoats go to London, cotton shirts go to Uganda, sleepwear goes to Belize, shoes go to Haiti, Levi's are coveted all over the world, and worn out promotional t-shirts are made into shoddy or wiping rags. In 2003, it was projected there would be a 3-5% increase in world fiber consumption which equals 2 million tons per year (http://bharattextile.com; Estur and Becerra, 2003). This presents a double-edged sword in that while at the same time it stimulates the economy (projected to add 10-20 new factories to meet the world market demand); it also gives rise to the increased problem of apparel and textile disposal. This paper provides a systems perspective that depicts the textiles recycling processes, particularly as it pertains to apparel. After that a micro-macro model using social systems theory will be presented. Finally, I will provide a synthesis of how systems theory provides a useful tool to project future trends for the textile and apparel recycling process. It is important to note that this work is based primarily on the processes as they are in the United States. My research is based on over five years of qualitative data collection on, primarily, apparel and other fashion products consumed throughout the United States and the world.
Keywords: Textile recycling; Environment; Systems theory; Qualitative research; Apparel; Social responsibility